Pemberian Pupuk Kandang Ayam dan Pupuk Organik Cair (POC) Limbah Ikan dapat Meningkatkann Pertumbuhan dan Produksi Tanaman Kacang Tanah (Arachis Hypogaea L.) - Al Rido Juniansyah; Erlita Chaniago; Iwan Hasrizart (Jurnal Agrofolium, 2026)
This study aims to determine the effect of Chicken Manure and Liquid Organic Fertilizer (POC) Fish Waste as well as the interaction of Chicken Manure and POC Fish Waste on the Growth and Production of Peanut Plants (Arachis Hypogeae L.). This research was conducted on Jalan Tuntungan II, Pancur Batu District, North Sumatra Province, from April to July 2025. This research used a Factorial Randomized Block Design with 2 factors studied and 3 replications where the first factor was chicken manure (K) consisting of 3 levels, namely K0 = (Control), K1 = (1 kg plot-1), K2 = (2 kg plot-1). The second factor was fish waste POC (I) consisting of 4 levels, namely I0 = (Control), I1 = (50 ml L-1 water per plot), I2 = (100 ml L-1 water per plot), I3 = (150 ml L-1 water per plot). The parameters observed were plant height (cm), flowering days (days), number of pods per sample (pods), number of pods per plot (pods), pod weight per sample (g) and pod weight per plot (g). The results of the study showed that the provision of chicken manure, fish waste POC and the interaction of the two treatments had no significant effect on all parameters of plant height (cm), flowering days (days), number of pods per sample (pods), number of pods per plot (pods), pod weight per sample (g), pod weight per plot (pods).